Haga su diagnóstico. - Cerda Sánchez, Ana Paola; García, Diego Reyes; Ustarán, David Monterrosas (Revista de la Facultad de Medicina de la UNAM)
The article presents a clinical case of a 7-year-old female patient who suffered a blunt trauma to the right side, which led to imaging studies to rule out injuries. The most common injuries in blunt abdominal trauma are discussed, highlighting the liver as the most affected organ and computed tomography as the best modality for evaluating liver injuries. Additionally, the classification of liver trauma according to the American Association for the Surgery of Trauma (AAST) is mentioned, and questions related to the diagnosis and treatment of this type of injury are presented.